Deformation modes and fracture behaviors of peak-aged Mg-Gd-Y alloys with different grain structures - Jiangli Ning; Jialiao Zhou; Bosong Gao; Chunlei Zhang; Hailong Shi; Liansheng Chen; Xiaojun Wang (Journal of Magnesium and Alloys)
The ductility and toughness of peak-aged (PA) Mg-RE alloys are significantly influenced by their grain structure characteristics. To investigate this issue, we examined PA Mg-8.24Gd-2.68Y (wt.%) alloys with two distinct grain structures: an extruded-PA sample with dynamic recrystallized (DRXed) fine grains and coarse hot-worked grains, and an extrusion-solution treated and PA sample with grown large equiaxed grains. The results showed that the extruded-PA sample demonstrated a favorable combination of tensile strength (426 MPa) and ductility (7.0 %). Although intergranular microcracks nucleated in the DRXed region due to strain incompatibility, crack propagation was impeded by the DRXed fine grains, inducing intrinsic and extrinsic toughening mechanisms. On the other hand, the hot-worked grains in the extruded-PA sample initiated transgranular cracks after a relatively high strain, attributed to the strain partitioning effect, ultimately leading to failure. In comparison, the solution-treated-PA sample exhibited lower tensile strength and ductility (338 MPa and 3.7 %, respectively). Intergranular cracks nucleated in the CG sample before necking, and the readily formed critical crack, facilitated by the large grain size, exhibited unstable crack growth, resulting in premature failure. This work offers valuable insights for designing high-performance PA Mg-RE alloys and preventing premature failure in practical applications.